DETERMINANT FACTORS OF PRODUCING ACCESSIBLE WEBSITE BY JOURNALISM COMPANIES IN MALAYSIA : - Ng, Chyi Horng, 1988-, author; Nurazean Maarop, Dr., supervisor; Sekolah Informatiks Termaju (Kuala Lumpur : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Sains (Informatiks)) - Universiti Teknologi Malaysia, 2016